CASE REPORT: BEYOND THE TOXICOLOGY SCREEN: RECOGNIZING THYROID STORM IN A PATIENT INITIALLY SUSPECTED OF SUBSTANCE-INDUCED CARDIOMYOPATHY - Ismail, Ihsan; Zuki, Rabeah Md; Nazri, Farehah Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid storm is a life-threatening endocrine emergency characterized by exaggerated hyperthyroidism. Its diverse clinical manifestations can sometimes mimic other acute conditions, leading to diagnostic challenges. We present a unique case of a young adult with thyroid storm whose initial presentation strongly suggested substance-induced cardiomyopathy. CASE A 29-year-old Malay male with a history of active smoking and drug abuse presented with a one-week history of non-productive cough and sudden onset of shortness of breath after physical exertion. On initial assessment, he exhibited marked restlessness, diaphoresis, and irregular narrow complex tachycardia on electrocardiogram (ECG). Urine toxicology was positive for amphetamine and methamphetamine, leading to an initial suspicion of substance-induced cardiomyopathy complicated by rapid atrial fibrillation. He was managed with anti-arrhythmics and non-invasive ventilation. However, persistent tachycardia and clinical deterioration necessitated intubation. A chest X-ray revealed cardiomegaly. Interestingly, routine thyroid function tests, which were ordered due to the patient's unexplained tachycardia, returned with a significantly suppressed thyroid-stimulating hormone (TSH) of <0.008 mIU/L and an elevated free thyroxine (FT4) of 64 pmol/L. This, coupled with a Burch-Wartofsky score of 65, strongly indicated thyroid storm. The initial diagnosis was revised accordingly. Despite aggressive management for thyroid storm, including anti-thyroid medications, beta-blockers, and supportive care, the patient developed acute infarcts in the right middle cerebral artery territory with subsequent hemorrhagic transformation and significant cerebral edema on serial computed tomography (CT) scans of the brain. Neurosurgical intervention was considered but declined by the family due to the guarded prognosis. The patient eventually succumbed to death due to massive cerebral infarct. This case highlights the importance of considering thyroid storm in the differential diagnosis of young adults presenting with acute cardiac symptoms and agitation, even in the presence of positive toxicology screens. The initial clinical picture and positive drug screen misleadingly pointed towards a primary cardiac etiology. The significantly abnormal thyroid function tests were crucial in establishing the correct diagnosis. While the exact mechanism of the cerebral infarction in this context remains unclear, it could be a rare complication of severe thyroid storm, potentially exacerbated by underlying substance abuse or other unidentified factors. This case underscores the need for a broad differential diagnosis and timely thyroid function testing in patients with unexplained acute cardiovascular symptoms, particularly when atypical features are present. CONCLUSION This case serves as a reminder of the protean manifestations of thyroid storm and the potential for diagnostic confusion with other acute conditions. A high index of suspicion and prompt laboratory investigations are essential for timely and accurate diagnosis, which is critical for improving patient outcomes in this life-threatening endocrine emergency.